A reflexive study of the continuous practice improvement of a global professional / Michael M Dent - Michael, M Dent (2016)
This thesis examines the career of a global professional as he moves across three continents whilst working for a large multi-national organisation. It describes the circle of Academe to Corporate and back to Academe. It builds the narrative from that of a student, to a practitioner, on to a learner and finally to that of a reflexive practitioner. The target audience for this thesis is both Academics and Practitioners. The single case study approach permits observations that can be utilised as building blocks in a theory of organisations and the individuals that work within them. This complex interaction of large numbers of variables produces chaos in some dimensions (in the sense that they are both un-forecastable and uncontrollable), undesirable consequences (through some deterministic interactions) and some predictors of success or failure at an individual level. This case study thesis is therefore applying a Grounded Theory methodology. Grounded Theory requires an in depth analysis of empirical material, it is not dependent on the ability to prove or disprove hypotheses. Marx tended to look on organisations and their managers as all with similar objectives and approaches. Critical analysis rejects this perspective and this thesis attempts to show how individual conflicts of interest can lead to undesirable consequences at organisational and societal levels. This has implications for a wide slew of legitimate State interests, including corporate taxation, legal Structure, Society etc. The thesis utilises an Action Research methodology employing a hermeneutic and interpretative approach. The stance taken is that of Critical Theory, that is to say with an objective ontology and subjective epistemology. It therefore rejects the Post-Modernism position of subjective ontologies and epistemologies whilst accepting that language is in itself value laden and requires careful interpretation. It is, however, written in a Post- Modernist style. In a sense it is an emic ethnographic investigation into the field (or iv society) of Marketing. It does, necessarily, possess autobiographical elements in order to apply the action research methodology but it is not in itself an autobiographical study. The strength of the action research approach is that a wide range of data is presented and is then subjected to evaluation and an ever decreasing spiral of supportive data based on warranted assertions is then provided in order to produce fresh insights into the field of the researcher with his living-theory Epistemology is a central theme within this thesis and the importance of warranted knowledge as an underwriter of validity and reliability is discussed. Similarly the link between tacit knowledge and luck is examined and found to be strongly connected. The danger of reflexive research is that there must necessarily exist a correlation between the subject of study and the psychology of the researcher, therefore, without knowledge of both, fuller understanding remains unobtainable, without these insight is impossible. Fundamentally the process of action, critical self-reflection and writing empowers the writer as a thinker and hence improving his capability of excellence in analysis and thus superior action in the future. The results produce insights both for future international professionals and also researchers and teachers in the field of business administration.